MEMS flexible artificial basilar membrane fabricated from piezoelectric aluminum nitride on an SU-8 substrate. (5th June 2017) - Jang, Jongmoon; Jang, Jeong Hun; Choi, Hongsoo
Abstract: In this paper, we present a flexible artificial basilar membrane (FABM) that mimics the passive mechanical frequency selectivity of the basilar membrane. The FABM is composed of a cantilever array made of piezoelectric aluminum nitride (AlN) on an SU-8 substrate. We analyzed the orientations of the AlN crystals using scanning electron microscopy and x-ray diffraction. The AIN crystals are oriented in the c -axis (0 0 2) plane and effective piezoelectric coefficient was measured as 3.52 pm V −1 . To characterize the frequency selectivity of the FABM, mechanical displacements were measured using a scanning laser Doppler vibrometer. When electrical and acoustic stimuli were applied, the measured resonance frequencies were in the ranges of 663.0–2369 Hz and 659.4–2375 Hz, respectively. These results demonstrate that the mechanical frequency selectivity of this piezoelectric FABM is close to the human communication frequency range (300–3000 Hz), which is a vital feature of potential auditory prostheses.